"The Awful Rowing toward God": Interpretation of Religious Experiences by Individuals with Bipolar Disorder - Ouwehand, Eva (Pastoral psychology, 2019)
Limited research has been conducted on the religious experiences of people with bipolar disorder (BD). Qualitative research indicates that the disentanglement of pathology and genuine religiosity is an important issue for persons with BD and that some patients experience discrepancy between the explanatory models of mental health care professionals and religious leaders. The current study explores the ways patients with BD interpret religious experiences they have had during illness episodes, how this interpretation changes over an individual's lifetime, and the expectations of treatment that persons with BD have regarding these religious experiences. Semi-structured interviews with 34 stable BD patients were conducted by a hospital chaplain and a psychiatrist trainee. The method of analysis was interpretative phenomenological analysis. For many participants, a religious quest originated after a religious experience during mania, and then a variety of medical and religious sources supported the interpretation process. Most participants endorsed mixed medical and religious explanations for their experiences and tried to distinguish between spiritual and pathological features. The interpretation process changed over time, influenced by religious affiliation and views, mood swings and the course of BD, and communication with others about the experiences. Discourse about the experiences was often problematic within treatment; a majority expressed the need for recognition of the spiritual value of the experiences, together with a critical sounding board for reflecting on their meaning and the influence of BD. More attention could be paid to the subject in treatment, and the expertise of hospital chaplains could contribute to this.